2011
DOI: 10.1593/neo.11624
|View full text |Cite
|
Sign up to set email alerts
|

Invasion Precedes Tumor Mass Formation in a Malignant Brain Tumor Model of Genetically Modified Neural Stem Cells

Abstract: Invasiveness, cellular atypia, and proliferation are hallmarks of malignant gliomas. To effectively target each of these characteristics, it is important to understand their sequence during tumorigenesis. However, because most gliomas are diagnosed at an advanced stage, the chronology of gliomagenesis milestones is not well understood. The aim of the present study was to determine the onset of these characteristics during tumor development. Brain tumor-initiating cells (BTICs) were established by overexpressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 26 publications
2
104
0
Order By: Relevance
“…A high capacity for dissemination is one of the defining features of gliomas (45,46), and this invasion process renders tumors more complex. Invading tumor cells escape at the periphery of the tumor mass and diffusely infiltrate the normal brain parenchyma (47).…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…A high capacity for dissemination is one of the defining features of gliomas (45,46), and this invasion process renders tumors more complex. Invading tumor cells escape at the periphery of the tumor mass and diffusely infiltrate the normal brain parenchyma (47).…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…In addition to repopulating tumors, TICs directly participate in the invasion process in vivo . For example, both primary GBM TICs (10) and H-Ras-transduced neural stem cells (11) invade brain tissue prior to forming the tumor mass. Moreover, hypoxia, which is often associated with the TIC niche (12) and the necrotic tumor core in which GBM TICs may reside, can enhance migration of GBM tumor cells through induction of the family of hypoxia-inducible factors (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The current model also doesn't take into account the role of some important players of the microenvironment that may affect the migration and growth of glioblastoma which include stromal cells such as fibroblasts, immune cells, and endothelial cells as well as growth factors and cytokines secreted by these cells. In a recent study [19], it was shown that intraparenchymal and perivascular glioma cell migration precede creation of tumor mass in the adult brain, suggesting the need for anti-invasion therapy for highly invasive glioblastoma. Our approach of optimal control of the core miR-451-AMPK control system may shed light on the development of a tool to deal with strategies in anti-invasion therapy.…”
Section: Resultsmentioning
confidence: 99%